PENGARUH CITRA MEREK, KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN KONSUMEN PADA DISTRO RSCH DI YOGYAKARTA - ADAM NUR FATONI (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to analyze the influence of brand image on consumer satisfaction, impact of service quality to customer satisfaction, and the influence of customer value on customer satisfaction, and the influence of brand image, service quality, and customer value on customer satisfaction together on customer satisfaction in distro RSCH Yogyakarta. The population in this study is that consumers distro RSCH in Yogyakarta examined by the authors include Brand (X1), Quality of Service (X2), Customer Value (X3) and the Consumer Satisfaction Y). The research sample was 100 consumers. Methods of data collection using questionnaires, while data analysis techniques using multiple regression analysis were supported by F test and T test and also test the classical assumption of normality test, multicollinearity, and heteroscedasticity test. The results of the study with rank of significance of 5% or 0.05 indicates that brand image significantly influence consumer satisfaction (0.023 <0.05), quality of service significantly influence consumer satisfaction (0.000 <0.05), and the value of the customer does not significantly influence consumer satisfaction (0593 <0.05). But simultaneously variable brand image, service quality, and customer value together influential on consumer satisfaction on the distributions RSCH Yogyakarta (0,000 < 0,05).